Perlindungan Hukum terhadap Anak sebagai Pelaku Tindak Pidana Bullying dan Gangster di SMPN 8 Cilegon - Surachman Surachman; Asmariyah Asmariyah; Saprudin Saprudin; Haris Fujiono; Ira Juhairannisa; Syavina Destriana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
School is an educational institution that aims to educate the nation. However, sometimes there are many problems, especially those related to students or students. Starting from cases of brawls, discipline, harassment, to bullying. Bullying is actually nothing new, but along with the times and changes in technology, there is also a lot of news that is viral and widely discussed. Bullying can also cause addiction for students and can form groups with certain members, which can even become potential gangsters in the future. The aim of this PKM in the field of law is one of the KKM programs for students from the 40 Cikerai Village groups at Bina Bangsa University as a form of concern for the rise in cases of bullying and gangsters at the secondary school level, especially Junior High Schools (SMP), which have a negative impact in the long term. The method for implementing PKM this time was a seminar on legal protection of the dangers of bullying and gangsterism among junior high school students. The results of this PKM conclude that there is a negative impact on bullying and gangsterism, both on physical, mental and psychological health. And can be caught in the law regarding bullying and gangsterism.